2007
DOI: 10.2214/ajr.06.0541
|View full text |Cite
|
Sign up to set email alerts
|

Internal Hernia After Gastric Bypass: Sensitivity and Specificity of Seven CT Signs with Surgical Correlation and Controls

Abstract: Mesenteric swirl is the best indicator of internal hernia after laparoscopic Roux-en-Y gastric bypass, and even minor degrees of swirl should be considered suspicious.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
119
0
5

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 204 publications
(133 citation statements)
references
References 18 publications
5
119
0
5
Order By: Relevance
“…2,3 A swirl sign on CT in a patient with abdominal pain should always raise the suspicion of an internal hernia. …”
Section: Discussionmentioning
confidence: 99%
“…2,3 A swirl sign on CT in a patient with abdominal pain should always raise the suspicion of an internal hernia. …”
Section: Discussionmentioning
confidence: 99%
“…According to Lockhart et al 10 , the laparoscopic Roux-en-Y gastric bypass resulted in reduction of perioperative complications, but the internal hernia remains a problem. The studies of Blachar et al 12 , who found 2.8% of internal hernias, and of Higa et al7, with 2.5%, corroborate this opinion.…”
Section: Ribas Ribas Ribasmentioning
confidence: 99%
“…Compared with the traditionally performed "open" surgery, the minimally invasive alternative, the laparoscopic Roux-en-Y gastric bypass (LRYGBP), has gained far wider acceptance because of fewer wound complications, shorter hospital stays, and better cosmetic results [7][8][9]. Likewise, postoperative intra-abdominal adhesions are less common.…”
Section: Introductionmentioning
confidence: 99%
“…The surgical defects leading to the prolapse of small bowel loops have been known to occur at four different sites: either at the incised transverse mesocolon; at the Petersen's space, which represents an opening between the mesocolon and the Roux limb mesentery; at the jejunojejunostomy mesenteric defect, known as mesojejunal hernia; or, finally, at the suture of the two jejunal loops, the biliopancreatic and the Roux limb, called jejunojejunal hernia [3,4,[6][7][8][9][10][11][12][16][17][18].…”
Section: Introductionmentioning
confidence: 99%